Improving Year 7 Students' Mathematics Communication Skills by The Discovery Learning Model - Dani, Ulima; Zubaidah, Tuti (Universitas Sebelas Maret, 2020)
One way to improve students' communication skills is by applying the Discovery Learning model. It can improve students' communication skills by enabling students to express ideas of their findings. Communication skills can be orally or in writing, and teachers need to motivate students to communicate actively. This study aims to determine Year 7 students' mathematics communication skills by the Discovery Learning model in mathematics learning. This was a quantitative research using a pre-experimental design with a one-group pretest-posttest. This research population was all Year 7 students in the school studied, and the sample was one class that was selected randomly. The research instruments were pre-test and post-test to explore students' communication skills. The results indicated that the Discovery Learning model could improve Year 7 students' mathematics communication skills. It is expected that this research may inform teachers and educators concerning the application of appropriate learning model for enhancing students’ communication skills.